Relationship Between Inclusive Leadership and Extra Role Behaviors in Higher Education - Long Wang ly; Guon Yi; Moolikay Allison (Inovasi Analisis Data, 2024)
Objective: The current study aimed to investigate the role of Inclusive Leadership (INL) by assessing its impact on Organizational Learning (OL), Innovative Work Behaviour (IWB), and Organizational Citizenship Behaviour (OCB). It examine the direct and indirect effects of INL on these outcomes by focusing on the mediating role of OL.Methods: Structural equation modeling was utilized for data from employees of different organizations. No data had to be gathered to examine relations between contructs (700 respondents)Results: The findings indicate substantial direct effects of INL on OL, IWB, and OCB. Moreover, OL served as a mediator between INL and IWB and OCB, which shows that organizational learning is critical in the process of transforming inclusive leadership into employee behavior.Novelty: The study provides theoretical and managerial implications by elucidating the mediating role of OL on the relationship of INL with vital employee behaviors. It sheds new light on the mechanisms by which inclusive leadership fosters innovation and citizenship behaviors.Theory and Policy Implications: The results indicate that organizations should promote inclusive leadership and invest in learning environments that will boost innovation and voluntary organizational behaviors. Insights,Data-driven insights,Policy planning,HR policies and practices,Organizational leadership,Leadership developmentHuman resource developmentLeadership and management.